2022
DOI: 10.3389/fpls.2021.812360
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polyamines in Root Plasma Membrane Enhanced the Tolerance of Plum Seedling to Osmotic Stress by Stabilizing Membrane Structure and Therefore Elevating H+-ATPase Activity

Abstract: Polyamines are small positively charged molecules in plants and play important functions in many biological processes under various environmental stresses. One of the most confounding problems relating to polyamines (PAs) in stresses is the lack of understanding of the mechanisms underlying their function(s). Furthermore, a limited number of studies have addressed this issue at the sub-cellular level, especially in tree plants under drought stress. Therefore, in this research, by simulating natural drought str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The effect of Put on PM-NR activity was different during non-stress and stress conditions. Recent studies showed that PAs conjugated to plasma membranes can increase plant tolerance to abiotic stress by stabilizing the membrane structure [ 81 ]. Exogenous PAs may also positively affect the level of NO 3 − ions in plant organs during abiotic stresses [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Put on PM-NR activity was different during non-stress and stress conditions. Recent studies showed that PAs conjugated to plasma membranes can increase plant tolerance to abiotic stress by stabilizing the membrane structure [ 81 ]. Exogenous PAs may also positively affect the level of NO 3 − ions in plant organs during abiotic stresses [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…PAs in plants also stabilize plasma membranes and significantly affect the activity of various ion transporters, both of which are important for growth and stress resistance [ 150 , 151 ]. A recent study found that treatments affecting the formation of conjugated forms of Spd and Spm correlated with drought resistance, root plasma membrane stability, and higher H + -ATPase activity [ 152 ]. Pas also interact with phytohormones to promote stress resistance ( Section 5.2.2 ).…”
Section: A Brief Review Of the Roles Of Polyamines In Plantsmentioning
confidence: 99%